New Insights Into Blood-Brain Barrier Maintenance: The Homeostatic Role of β-Amyloid Precursor Protein in Cerebral Vasculature - Ristori, Emma; Donnini, Sandra; Ziche, Marina (Frontiers in Physiology, 2020)
Cerebrovascular homeostasis is maintained by the blood-brain barrier (BBB), a highly selective structure that separates the peripheral blood circulation from the brain and protects the central nervous system. Dysregulation of BBB function is the precursor of several neurodegenerative diseases including Alzheimer's disease (AD) and Cerebral Amyloid Angiopathy (CAA), both related to β-amyloid (Aβ) accumulation and deposition. The origin of BBB dysfunction before and/or during CAA and AD onset is not known. Several studies raise the possibility that vascular dysfunction could be an early step in these diseases and could even precede significant Aβ deposition. Though accumulation of neuron-derived Aβ peptides is considered the primary influence driving AD and CAA pathogenesis, recent studies highlighted the importance of the physiological role of the β-Amyloid Precursor Protein (APP) in endothelial cell homeostasis, suggesting a potential role of this protein in maintaining vascular stability. In this review, we will discuss the physiological function of APP and its cleavage products in the vascular endothelium. We further suggest how loss of APP homeostatic regulation in the brain vasculature could lead toward pathological outcomes in neurodegenerative disorders.